2014
DOI: 10.7314/apjcp.2014.15.9.4061
|View full text |Cite
|
Sign up to set email alerts
|

No Detection of 'High-risk' Human Papillomaviruses in a Group of Iranian Women with Breast Cancer

Abstract: Asian Pac J Cancer Prev, 15 (9), [4061][4062][4063][4064][4065] IntroductionBreast cancer is the second most common cancer in the world, accounts for 25% of all cancers (excluding nonmelanoma skin cancers) in women (GLOBOCAN, 2012). According to recently published data, the overall cancer incidence in Iran has been 110 per 100,000 in men and 98 per 100,000 in women in 2006. Among Iranian women, breast cancer is the leading cause of cancer morbidity and mortality, even though its incidence is among the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
2
15
3
Order By: Relevance
“…The values identified in our study were lower than those described in a meta-analysis of 29 published studies, in which the prevalence rates of HPV infection were 23% in BC samples and 12.9% in normal cases. However, in contrast to the present study findings, studies conducted in France, Iran and Switzerland failed to detect the presence of HR-HPVs in benign breast tissue specimens of the related population [25][26][27].…”
Section: Discussioncontrasting
confidence: 99%
“…The values identified in our study were lower than those described in a meta-analysis of 29 published studies, in which the prevalence rates of HPV infection were 23% in BC samples and 12.9% in normal cases. However, in contrast to the present study findings, studies conducted in France, Iran and Switzerland failed to detect the presence of HR-HPVs in benign breast tissue specimens of the related population [25][26][27].…”
Section: Discussioncontrasting
confidence: 99%
“…This observation is consistent with the findings of other studies from different geographical areas which reported 32% and 18% of benign tissues were positive in Turkish and Australian populations, respectively2233. However in contrast to our findings, studies conducted in France, Iran, and Switzerland failed to detect the presence of HR-HPVs in benign breast tissue specimens of the related population232434.…”
Section: Discussioncontrasting
confidence: 99%
“…50 Additionally, a few studies from Iran showed varying HPV prevalence in breast cancer (14-49%) in Iranian women. 45,[51][52][53] On the other hand, it is important to highlight that a study on cervical samples in Qatari women found HPV prevalence of 55%, which also supports our data. 54 Indeed, one of the key findings in our study is the predominance of HPV genotypes -52 and −56 in breast cancer from Qatari women.…”
Section: Discussionsupporting
confidence: 90%